2021
DOI: 10.1002/met.2009
|View full text |Cite
|
Sign up to set email alerts
|

Past and future drought trends, duration, and frequency in the semi‐arid Urmia Lake Basin under a changing climate

Abstract: Although the Urmia Lake has undergone remarkable drought conditions within the past decades mainly due to climate change, drought studies covering the entire Urmia Lake Basin and all drought aspects are lacking. The present study investigated the spatial and temporal drought conditions in the Urmia Lake Basin for the past and future (2021-2050 and 2051-2080) periods using five general circulation models (GCMs) under the IPCC (Intergovernmental Panel on Climate Change) scenarios RCP 2.6, RCP 4.5, and RCP 8.5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 75 publications
1
9
0
2
Order By: Relevance
“…To investigate the experienced drought incidents and their association with the water storage and the lake's water level variations over the LUB, two traditional drought indicators of scPDSI and SPEI are used in this study. Although the Standardized Precipitation Index (SPI) is overwhelmingly utilized through the majority of drought evaluation studies, the authors ignored using it over the LUB because it was suggested that SPEI outperforms SPI in the LUB (Mirgol et al, 2021). It can be justified based on the fact that the LUB is more affected by increasing temperature and ET impacts rather than precipitation variations themselves (Mirgol et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the experienced drought incidents and their association with the water storage and the lake's water level variations over the LUB, two traditional drought indicators of scPDSI and SPEI are used in this study. Although the Standardized Precipitation Index (SPI) is overwhelmingly utilized through the majority of drought evaluation studies, the authors ignored using it over the LUB because it was suggested that SPEI outperforms SPI in the LUB (Mirgol et al, 2021). It can be justified based on the fact that the LUB is more affected by increasing temperature and ET impacts rather than precipitation variations themselves (Mirgol et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite what we might expect, the most intense droughts were detected with SPI. Although most research refers to the greater capacity of SPEI to identify droughts [92,93,94] there is no common agreement regarding the severity detected. In some studies in semi-arid regions higher intensities were detected with SPI [94,95,96], whilst in others a higher severity was always identified with SPEI [97].…”
Section: Discussionmentioning
confidence: 99%
“…One of the very common methods for calculating SPI and SPEI is the use of software packages such as the SPEI package in R studio (Silva et al 2022;Mirgol et al 2021), which strictly follows a xed mean method. And so, the user should be cautioned on the reliability of drought intensities for years early in the record, as these will be relative to meteorological conditions of the subsequent years and not their own historical ranges.…”
Section: Discussionmentioning
confidence: 99%